2014
DOI: 10.1016/j.mjafi.2013.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Rate of decline in CD4 count in HIV patients not on antiretroviral therapy

Abstract: There was a progressive decline in the CD4 count following HIV infection. An understanding of the influence of decline in CD4 count in HIV patients not on ART is important for clinical management of HIV disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…It is widely known that the progression of HIV disease is directly related with the time of infection, with late HIV infections associated with CD4 + cell depletion and increased HIV replication [ 50 ]. To determine whether the time of HIV infection was a confounding factor in our study, we analysed the effect of HPgV viral load conditions according to recent or late HIV infection ( S1 Table ).…”
Section: Discussionmentioning
confidence: 99%
“…It is widely known that the progression of HIV disease is directly related with the time of infection, with late HIV infections associated with CD4 + cell depletion and increased HIV replication [ 50 ]. To determine whether the time of HIV infection was a confounding factor in our study, we analysed the effect of HPgV viral load conditions according to recent or late HIV infection ( S1 Table ).…”
Section: Discussionmentioning
confidence: 99%
“…This may have resulted in biased model estimates for cVL 2 . However, we did control for baseline CD4 count which, although perhaps not ideal due to inter-patient variability in the rate of CD4 decline prior to ART [53], is frequently used as a surrogate marker for duration of infection [54]. Further, approaches for adjusting for pre-ART VLs, as summarized in a prior study [13], may be of limited value as they are dependent on an individual’s innate viral controlling ability.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results revealed that PLHIV with a low risk of ED had significantly higher self-adherence scores compared to those with a high risk of ED, corresponding with the high discipline of ART administering among PLHIV with a low risk of ED. The CD4 level was also significantly higher in the high-risk ED group, which may help prevent opportunistic infections [25]. The limitations of this study were that information on participants' physical activity was not collected and just one food record was collected for each participant, which might not be enough to validate the composition of food being consumed because they may consume different food during other working days and weekend days.…”
Section: Discussionmentioning
confidence: 96%